Laminate film

The laminated film structure, featuring a polypropylene substrate and an inorganic thin film layer, addresses the challenges of gas barrier and adhesive performance in packaging materials, while being environmentally friendly and easy to manufacture.

JP2025039697AActive Publication Date: 2025-03-21TOYOBO CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2025002342
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-07-21
Filing Date
2025-01-07
Publication Date
2025-03-21
Estimated Expiration
2041-07-14

AI Technical Summary

Technical Problem

Existing packaging materials face challenges in achieving both excellent gas barrier performance and sufficient adhesive strength while being environmentally friendly, particularly due to issues with humidity dependence, material recycling, and the use of organic solvents.

Method used

A laminated film structure is developed, comprising a polypropylene film substrate with a surface layer and an inorganic thin film layer, where the haze is 5% or less, and specific surface roughness and adhesion properties are maintained to enhance gas barrier and adhesive performance.

Benefits of technology

The laminated film achieves improved gas barrier properties and adhesion, while minimizing environmental impact, and is suitable for packaging applications with reduced processing steps and material usage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039697000006
    Figure 2025039697000006
  • Figure 2025039697000001
    Figure 2025039697000001
  • Figure 2025039697000002
    Figure 2025039697000002
Patent Text Reader

Abstract

To provide a laminate film which is a film capable of forming a lamination constitution composed of a substantially single resin type that mainly contains a polypropylene film and has less environmental loads, and has gas barrier property and adhesion required for a packaging material.SOLUTION: A laminate film has a surface layer (B) composed of a polypropylene-based resin composition on one surface of a base material layer (A) containing a polypropylene-based resin as a main component, and a surface layer (C) composed of a polypropylene-based resin composition on the other surface of the base material layer (A), and has an inorganic thin film layer (D) stacked on the surface layer (B), wherein the laminate film has tensile elastic modulus in an MD direction of 2.6 GPa or less and tensile elastic modulus in a TD direction of 4.1 GPa or more, and a haze of 5% or less, and the surface on the inorganic thin film layer (D) side of the laminate film satisfies requirements (I) to (IV). (I) Arithmetic average roughness (Ra) measured in the rage of 2 μm square by a scanning probe microscope is 4.5 nm or more and 9.0 nm or less. (II) Martens hardness is 310 N / mm2 or less. (III) Water contact angle is 10° or more and 75° or less. (IV) Central surface average roughness (SRa) measured by three-dimensional roughness meter is 0.010 μm or more and 0.040 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate film, and more specifically to a gas barrier laminate film that imposes a small environmental load during production and disposal, and that combines both excellent gas barrier performance and sufficient adhesive strength between layers for use as a packaging material.

[0002] In recent years, regulations aimed at reducing the use of disposable plastics have been strengthened in Europe and other countries around the world. Behind this lies the growing international awareness of resource circulation and the worsening waste problems in emerging countries. For this reason, there is a demand for environmentally friendly products from the perspective of the 3Rs (recycle, reuse, reduce) for plastic packaging materials required for food, medicines, etc.

[0003] The performance required for the aforementioned environmentally friendly packaging materials includes (1) being made from materials that are easy to recycle, (2) having gas barrier performance that can block various gases and extend the shelf life, and (3) having a laminate structure that has a low environmental impact (for example, not using organic solvents, using only small amounts of materials, and being recyclable by converting them into mono-materials).

[0004] In recent years, the use of polypropylene films has been attracting attention in order to make the above (2) and (3) possible. Polypropylene films are used for a wide range of purposes, such as packaging for food and various other products, electrical insulation, and surface protection films. Polypropylene films are capable of exhibiting high water vapor barrier properties due to their molecular structure. Furthermore, since polypropylene- or polyethylene-based heat seal resins are generally used as sealants to be bonded to the surface substrate film, for example, by using a polypropylene film for the surface substrate and an unstretched polypropylene sheet for the sealant, it is possible to achieve mono-materialization of the entire packaging material while maintaining gas barrier properties, and to design packaging materials that are easy to recycle and are environmentally friendly.

[0005] However, with regard to the gas barrier property of (2) above, although polypropylene film has water vapor barrier property, the value is not sufficient compared to, for example, transparent inorganic vapor-deposited polyester film, which is generally considered to have excellent water vapor barrier property, and there is a problem that the oxygen barrier property is very poor. In response to this, films have been used in which a polymer resin composition, which is generally considered to have a relatively high oxygen barrier property, such as polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyvinylidene chloride resin, polyacrylonitrile, etc., is laminated on a polypropylene film (for example, see Patent Documents 1 to 3).

[0006] However, the gas barrier coating film made of the above-mentioned polyvinyl alcohol or ethylene vinyl alcohol copolymer polymer resin composition has a high humidity dependency, so that the gas barrier property is reduced under high humidity conditions, and the water vapor barrier property and water-resistant adhesion are not sufficient. Also, polyvinylidene chloride resin and polyacrylonitrile have a low humidity dependency, but have problems in that the water vapor barrier property is not sufficient and there is a high risk of generating harmful substances when disposed of or incinerated.

[0007] Furthermore, all of the above-mentioned barrier coat layers needed to be laminated to a thickness of 1 μm or more in order to achieve sufficient barrier performance. If the barrier coat layer was too thick, it could become a source of impurities during recycling, making recycling itself difficult. It was also not suitable from the perspective of mono-materialization using a single material. Furthermore, there were issues with printing defects due to unevenness and irregularities in the coating during processing such as printing.

[0008] To address these problems, gas barrier laminates are generally used in which a thin metal film made of aluminum or the like or a thin inorganic film made of an inorganic oxide such as silicon oxide or aluminum oxide is formed on the surface of a plastic substrate film such as a polyester film. Among these, those in which a thin inorganic oxide film such as silicon oxide, aluminum oxide, or a mixture thereof is formed are widely used because they do not require the use of aluminum foil, are transparent so that the contents can be confirmed, and furthermore, the formed film is very thin and does not impede recyclability.

[0009] A method has also been disclosed for imparting gas barrier properties to polypropylene films by laminating an inorganic thin film (e.g., Patent Document 4). However, since the molecules of polypropylene films are nonpolar, the surface energy is small, and it has been pointed out that the adhesion is therefore insufficient when processing inorganic thin films.

[0010] In addition, when forming an inorganic thin film layer, there is a problem not only with adhesion but also with the protruding parts due to surface unevenness, which makes it impossible to form a thin film, resulting in poor barrier properties. On the other hand, biaxially oriented polypropylene film has poor slipperiness due to its excellent flexibility and flatness, and blocking occurs when films stick to each other, so anti-blocking agents are generally added to form surface unevenness. As a result, the uneven surface that is formed makes it difficult to form a thin film by deposition or coating, which leads to problems such as poor barrier properties.

[0011] As a countermeasure to such problems, various methods for improving polypropylene films have been proposed, and for example, a method has been disclosed in which branched polypropylene is mixed with propylene resin, and the β crystals of polypropylene are transformed into α crystals to form unevenness on the film surface, thereby improving the slipperiness substantially without using an inorganic or organic antiblocking agent (see, for example, Patent Document 5, etc.). However, since only homopolypropylene with high stereoregularity is used, the surface is hard, and no consideration is given to adhesion when used for processing such as vapor deposition, coating, and lamination.

[0012] On the other hand, a method has been disclosed in which antistatic agents are eliminated as much as possible, and the difference in MFR between polypropylene resin and a copolymer of propylene and ethylene and / or an α-olefin having 4 or more carbon atoms is used to form surface irregularities in the resin itself on the surface layer of the film, thereby improving adhesion when laminated with ink or other films (see, for example, Patent Document 6, etc.). However, the arithmetic mean roughness (SRa) of the surface layer is high, which makes thin film formation by vapor deposition or coating insufficient, and may result in poor barrier properties. In addition, there is no antiblocking agent on one surface of the film, and wrinkles or blocking may occur in the rolled state.

[0013] As an alternative to improving the substrate, it is possible to improve adhesion by providing a separate organic solvent-based coating layer on the surface of the substrate, which contributes to adhesion and barrier properties, but the adhesive strength of this coating is insufficient.In addition, the coating process increases the number of processing steps, and the use of organic solvents is undesirable from the perspective of reducing the environmental impact, so it has been desired to achieve adhesive strength without an adhesive layer formed by coating. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] JP 2000-52501 A [Patent Document 2] Japanese Patent Application Publication No. 4-359033 [Patent Document 3] JP 2003-231221 A [Patent Document 4] International Publication No. 2017 / 221781 [Patent Document 5] International Publication No. 2007 / 094072 [Patent Document 6] International Publication No. 2018 / 142983 Summary of the Invention [Problem to be solved by the invention]

[0015] The barrier properties and adhesive properties of the above Patent Documents 1 to 4 were insufficient. Patent Documents 5 and 6 did not consider improving the barrier properties and adhesive properties of the inorganic thin film layer. Furthermore, none of the documents designed a material that satisfied the performance required for the above-mentioned environmentally friendly packaging material.

[0016] The present invention has been made in view of the above problems in the prior art. In other words, the object of the present invention is to provide a laminate film that can form a laminate structure composed of almost a single resin type that has a low environmental impact, mainly consisting of a polypropylene film, and that has the necessary performance properties required for packaging materials, such as gas barrier properties, adhesion, and processability. [Means for solving the problem]

[0017] The inventors have discovered that by designing a specific polypropylene film base layer tailored to the required performance and laminating an inorganic thin film layer thereon, it is possible to provide a film that significantly improves gas barrier performance and adhesion and also has a low environmental impact, thereby completing the present invention.

[0018] That is, the present invention comprises the following: 1. A laminate film having a surface layer (B) on one surface of a base layer (A) mainly composed of a polypropylene resin and a surface layer (C) on the other surface of the base layer (A), and further having an inorganic thin film layer (D) laminated on the surface layer (B), wherein the haze of the laminate film is 5% or less, and the surface of the laminate film on the inorganic thin film layer (D) side satisfies the following requirements (I) to (IV). (I) The arithmetic mean roughness (Ra) measured by a scanning probe microscope is 4.5 nm or more and 9.0 nm or less. (II) Martens hardness 310N / mm 2 below (III) Water contact angle is 75° or less (IV) The center surface average roughness (SRa) measured by a three-dimensional roughness gauge is 0.010 μm or more and 0.040 μm or less. 2. The oxygen permeability of the laminated film in an environment of 23°C x 65% RH is 60cc / m 2 ·d·atm or less, and water vapor permeability is 4g / m under 40℃×90%RH environment 2 1. The laminate film according to claim 1, wherein the thickness of the laminate film is 1.·d or less. 3. The laminate film according to 1 or 2, characterized in that, when the oxygen permeability value of the laminate film measured under conditions of 23°C × 65% RH is (A) and the oxygen permeability value of the laminate film measured under conditions of 23°C × 80% RH is (B), the barrier value deterioration rate under high temperature and high humidity conditions represented by the following formula is 130% or less. Barrier value deterioration rate under high temperature and high humidity conditions (%) = (B / A) x 100 Formula (1) 4. The laminate film according to any one of 1. to 3., wherein the center surface average roughness (SRa) of the surface layer (C) side of the laminate film measured with a three-dimensional roughness meter is 0.020 μm or more. 5. The Martens hardness of the surface of the surface layer (C) of the laminated film is 270 N / mm 2 The laminate film according to any one of 1. to 4., characterized in that: 6. The laminate film according to any one of claims 1 to 5, wherein the thickness of the laminate film is 9 µm to 200 µm. 7. A packaging material comprising the laminate film according to any one of 1. to 6. above and an olefin-based sealant layer laminated on one side of the laminate film. Effect of the Invention

[0019] By using this technique, the present inventors have been able to provide a laminated film that is environmentally friendly and has the necessary properties, such as barrier properties and adhesive properties, required for packaging materials. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is a diagram showing a method for measuring the air release time of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described in detail below. The laminate film of the present invention is a laminate film having a surface layer (B) on one surface of a base layer (A) mainly composed of a polypropylene-based resin, a surface layer (C) on the other surface of the base layer (A), and further having an inorganic thin film layer (D) laminated on the surface layer (B), wherein the haze of the laminate film is 5% or less, and the surface of the laminate film on the inorganic thin film layer (D) side satisfies the following requirements (I) to (IV). (I) The arithmetic mean roughness (Ra) measured by a scanning probe microscope is 4.5 nm or more and 9.0 nm or less. (II) Martens hardness 310N / mm 2 The following is the result. (III) The water contact angle is 75° or less. (IV) The center surface average roughness (SRa) measured by a three-dimensional roughness gauge is 0.010 μm or more and 0.040 μm or less. Each layer of the laminated film will now be described.

[0022] [Base film layer] (1) Base material layer (A) The base layer (A) mainly composed of a polypropylene-based resin constituting the laminated film of the present invention is preferably a biaxially oriented film, and the polypropylene used in the layer may be a polypropylene copolymerized with 0.5 mol % or less of ethylene and / or an α-olefin having 4 or more carbon atoms. Such copolymerized polypropylene is also included in the polypropylene of the present invention (hereinafter, polypropylene). The copolymerization component is preferably 0.3 mol % or less, more preferably 0.1 mol % or less, and a completely homopolypropylene containing no copolymerization component is most preferred. When ethylene and / or an α-olefin having 4 or more carbon atoms is copolymerized in an amount exceeding 0.5 mol %, the crystallinity and rigidity are too low, and the thermal shrinkage rate at high temperatures may become large. Such resins may be blended and used.

[0023] The mesopentad fraction ([mmmm]%) measured by 13C-NMR, which is an index of stereoregularity of the polypropylene constituting the base layer (A) of the polypropylene-based laminate film of the present invention, is preferably 98 to 99.5%, more preferably 98.1% or more, and even more preferably 98.2% or more. If the mesopentad fraction of the polypropylene is small, the elastic modulus will be low and the heat resistance may be insufficient. 99.5% is the practical upper limit.

[0024] The mass average molecular weight (Mw) of the polypropylene constituting the base layer (A) of the polypropylene-based laminate film of the present invention is preferably 180,000 to 500,000. If the Mw is less than 180,000, the melt viscosity is low, so the resin is not stable during casting, and film-forming properties may be poor. If the Mw is more than 500,000, the amount of components with a molecular weight of 100,000 or less becomes 35% by mass, and the heat shrinkage rate at high temperatures deteriorates. A more preferred lower limit of Mw is 190,000, even more preferably 200,000, and a more preferred upper limit of Mw is 320,000, even more preferably 300,000, and particularly preferably 250,000.

[0025] The number average molecular weight (Mn) of the polypropylene constituting the base layer (A) of the polypropylene-based laminate film of the present invention is preferably 20,000 to 200,000. If it is less than 20,000, the melt viscosity is low, so that the film-forming property may be deteriorated due to instability during casting, whereas if it exceeds 200,000, the heat shrinkage rate at high temperatures is deteriorated. A more preferable lower limit of Mn is 30,000, even more preferably 40,000, and particularly preferably 50,000, and a more preferable upper limit of Mn is 80,000, even more preferably 70,000, and particularly preferably 60,000.

[0026] Furthermore, the Mw / Mn, which is an index of molecular weight distribution, of the polypropylene constituting the base layer (A) is preferably 2.8 to 10, more preferably 2.8 to 8, still more preferably 2.8 to 6, and particularly preferably 2.8 to 5.4. The lower limit is preferably 3 or more, and more preferably 3.3 or more. The molecular weight distribution of polypropylene can be adjusted by polymerizing components of different molecular weights in a series of plants in multiple stages, blending components of different molecular weights offline in a kneader, blending catalysts with different performance properties and polymerizing them, or using a catalyst that can achieve the desired molecular weight distribution.

[0027] When the polypropylene constituting the base layer (A) of the polypropylene-based laminate film of the present invention has an Mw / Mn in the range of 2.8 to 5.4, it preferably has a melt flow rate (MFR; 230° C., 2.16 kgf) of 2 g / 10 min to 20 g / 10 min. The lower limit of the MFR of the polypropylene of the base layer (A) is more preferably 3 g / 10 min, further preferably 4 g / 10 min, and particularly preferably 5 g / 10 min. The upper limit of the MFR of the polypropylene constituting the base layer (A) is more preferably 15 g / 10 min, and further preferably 12 g / 10 min. When the Mw / Mn and MFR of the polypropylene constituting the base layer (A) are within this range, the heat shrinkage rate at high temperatures can be kept small, and the adhesion to the cooling roll is good, resulting in excellent film formability.

[0028] (2) Surface layer (B) The arithmetic mean roughness (Ra) of the surface of the surface layer (B) side of the polypropylene-based laminate film of the present invention measured by a scanning probe microscope (AFM) is preferably 3.0 nm or more and 5.5 nm or less. The arithmetic mean roughness (Ra) is determined in accordance with the definition of arithmetic mean roughness described in JIS-B0601 (1994) after measuring the X and Y directions in a dynamic mode using a scanning probe microscope (AFM) with a measurement length of 2 μm in both directions and correcting the obtained image (tilt, line fit, noise line removal).

[0029] The arithmetic mean roughness Ra of a 2 μm square area measured by AFM is an index that indicates the unevenness of the resin itself other than the relatively large peaks and valleys formed by the antiblocking agent and the lubricant, and is related to the adhesion to the inorganic thin film layer. If the arithmetic mean roughness (Ra) is less than 3.0 nm, the surface area of ​​the surface layer (B) is small, which causes a problem of reduced adhesion. If the arithmetic mean roughness (Ra) exceeds 5.5 nm, the surface unevenness is large, which causes gaps during the formation of the inorganic thin film, resulting in poor barrier properties. The arithmetic mean roughness (Ra) of the surface on the surface layer (B) side is more preferably 3.2 nm or more, even more preferably 3.3 nm or more, particularly preferably 3.5 nm or more, and most preferably 4.0 nm or more. In order to make the arithmetic mean roughness (Ra) of the surface on the surface layer (B) side 3.0 nm or more and 5.5 nm or less, it is preferable to use a mixture of two or more polypropylene resins with different melt flow rates (MFR) as the polypropylene resin composition forming the surface layer (B). In this case, the difference in MFR is preferably 3 g / 10 min or more, more preferably 3.5 g / 10 min or more. As mentioned above, it is assumed that if the difference in melt flow rate (MFR) between two or more polypropylene resins in a polypropylene resin mixture is different, the crystallization speed and degree of crystallization of each polypropylene will be different, which will easily cause surface irregularities. However, if the crystallization degree of polypropylene is high or the cooling rate of the unstretched sheet during film production is slow, the surface irregularities caused by spherulites will become large, or if the stretching temperature is too high during longitudinal or transverse stretching, whitening will occur and the surface irregularities will become large, which may cause the arithmetic average roughness (Ra) to exceed 5.5, so care must be taken.

[0030] As polypropylene resins with a smaller MFR, polypropylenes copolymerized with ethylene and / or α-olefins having 4 or more carbon atoms can be used. Examples of α-olefins having 4 or more carbon atoms include 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. In addition, polar maleic acid and the like can be used as other copolymerization components. The total amount of ethylene and / or α-olefins having 4 or more carbon atoms and other copolymerization components is preferably 8.0 mol% or less. If copolymerized in excess of 8.0 mol%, the film may whiten and have a poor appearance, or may become sticky, making film formation difficult. These resins may be used in combination of two or more kinds. When blended, each resin may be copolymerized in an amount exceeding 8.0 mol%, but the blend preferably contains 8.0 mol% or less of monomers other than propylene in monomer units. As the polypropylene resin having a larger MFR, the above-mentioned copolymer polypropylene can be used, or a homopolypropylene resin can be used.

[0031] In addition, the polypropylene resin composition constituting the surface layer (B) of the polypropylene-based laminated film of the present invention preferably has an MFR of 1.0 g / 10 min to 10.0 g / 10 min. The lower limit of the MFR of the polypropylene resin composition constituting the surface layer (B) is more preferably 2.0 g / 10 min, even more preferably 3.0 g / 10 min, and particularly preferably 4.0 g / 10 min. The upper limit of the MFR of the polypropylene resin composition constituting the surface layer (B) is more preferably 9.0 g / 10 min, even more preferably 8.0 g / 10 min, and particularly preferably 5.5 g / 10 min. Within this range, the film formability is good and the appearance is excellent. If the MFR of the polypropylene resin composition constituting the surface layer (B) is smaller than 1.0 g / 10 min, when the MFR of the polypropylene constituting the base layer (A) is large, the viscosity difference between the base layer (A) and the surface layer (B) becomes large, and unevenness (unevenness of the original roll) is likely to occur during film formation. If the MFR of the polypropylene resin composition constituting the surface layer (B) exceeds 10 g / 10 min, the adhesion to the cooling roll will be poor, air will be entrapped, the smoothness will be poor, and there is a risk that many defects will occur due to this.

[0032] In addition, the surface of the surface layer (B) of the polypropylene-based laminate film is preferably 0.010 μm or more and 0.040 μm or less by a three-dimensional roughness meter, regardless of the presence or absence of an inorganic thin film (D). The central surface average roughness SRa is measured using a three-dimensional roughness meter with a stylus pressure of 20 mg, a measurement length of 1 mm in the X direction, a feed pitch of 2 μm in the Y direction, 99 lines recorded, a height magnification of 20000 times, and a cutoff of 80 μm, and is determined in accordance with the definition of arithmetic average roughness described in JIS-B0601 (1994). The central surface average roughness (SRa) of the surface of the surface layer (B) is more preferably 0.012 μm or more and 0.038 μm or less, more preferably 0.015 μm or more and 0.036 μm or less, and particularly preferably 0.020 μm or more and 0.034 μm or less. Regardless of whether or not an inorganic thin film (D) is present, if the surface of the surface layer (B) has a center plane average roughness (SRa) of less than 0.010 μm, the surface unevenness is small, and the film's slipperiness, air escape time between films, and blocking resistance are deteriorated. If the center plane average roughness (SRa) of the surface of the surface layer (B) exceeds 0.040 μm, the antiblocking agent may penetrate the thin film layer when laminating the inorganic thin film layer (D), or a thin film may not be formed on the side of the convex part, resulting in reduced barrier properties and poor adhesion. There are several methods for keeping the center plane average roughness (SRa) of the surface of the surface layer (B) within the specified range, but it can be adjusted by the average particle size and amount of the antiblocking agent added.

[0033] The antiblocking agent can be appropriately selected from inorganic particles such as silica, calcium carbonate, kaolin, and zeolite, and organic particles such as acrylic, polymethacrylic, and polystyrene. Among these, it is particularly preferable to use silica or polymethacrylic particles. The preferred average particle size of the antiblocking agent is 1.0 to 3.0 μm, and more preferably 1.0 to 2.7 μm. The average particle size is measured by taking a photograph with a scanning electron microscope, measuring the Feret's diameter in the horizontal direction using an image analyzer, and expressing the average value. There are no particular limitations on the amount of anti-blocking agent added, so long as the amount added to the surface layer (B) and surface layer (C) is adjusted so that the haze, dynamic friction coefficient, center surface average roughness (SRa), and air release time are within the specified ranges.

[0034] The surface wetting tension of the surface layer (B) of the polypropylene-based laminated film of the present invention is preferably 38 mN / m or more. The wetting tension represents the surface tension (mN / m) of a mixed liquid reagent determined to wet the film surface, and is related to the wettability of printing inks and adhesives. If the wetting tension is 38 mN / m or more, the adhesion to the adhesive used for deposition film, coating film, and lamination with other member films is improved. In order to make the wetting tension 38 mN / m or more, additives such as antistatic agents and surfactants are usually used, but these methods have the effect of reducing the surface resistance value, so it is preferable to carry out physicochemical surface treatments such as corona treatment and flame treatment. For example, in the corona treatment, it is preferable to use a preheat roll and a treatment roll and perform discharge in the air.

[0035] The Martens hardness of the surface layer (B) of the polypropylene-based laminated film of the present invention is 310 N / mm 2 The Martens hardness is a value that indicates the hardness of a resin when a dynamic ultra-microhardness tester is used to press a needle tip with a curvature radius of 0.1 μm or less into the surface by about 0.1 μm. Preferably, the hardness is 305 N / mm 2 Less than 300N / mm 2 The following is the result. Martens hardness 310N / mm 2 If the Martens hardness exceeds 310N / mm, the surface becomes hard, the conformability of the resin surface during processing becomes poor, and the adhesive strength decreases. 2To achieve a hardness below this level, ethylene and / or an α-olefin with 4 or more carbon atoms, or other copolymerization components can be added. It is also possible to lower the Martens hardness by lowering the film stretch ratio and decreasing the orientation of the molecular chains. Note that care must be taken because the film may become brittle and hard due to radiant heat during the formation of the inorganic thin film layer, or components derived from the base material may bleed out and harden the film. The Martens hardness of the surface layer (B) of the polypropylene-based laminated film of the present invention is 200 N / mm 2 It is preferable that the resistance is equal to or higher than 210 N / mm 2 That's all.

[0036] (3) Surface layer (C) The surface of the surface layer (C) of the polypropylene-based laminated film of the present invention preferably has a center surface average roughness (SRa) of 0.020 μm or more as measured by a three-dimensional roughness meter. The center surface average roughness (SRa) of the surface layer (C) is more preferably 0.022 μm or more, even more preferably 0.025 μm or more, and particularly preferably 0.028 μm or more. If the center surface average roughness (SRa) of the surface layer (C) is less than 0.020 μm, the surface unevenness is small, and the slipperiness of the film, the air release time between the films, and the blocking resistance are deteriorated. There are several methods for setting the center surface average roughness (SRa) of the surface layer (C) within the specified range, and it is possible to adjust it by the average particle size and the amount of the antiblocking agent added. The surface layer (C) of the polypropylene-based laminate film of the present invention preferably has a center surface average roughness (SRa) of 0.040 μm or less as measured by a three-dimensional roughness meter.

[0037] In addition, the Martens hardness of the surface layer (C) of the polypropylene-based laminated film is 270 N / mm 2 It is preferable that the load is 275N / mm or more. 2 More preferably, 280N / mm 2 More preferably, 285N / mm 2 That's all. Martens hardness is 270N / mm 2If the hardness is less than 270N / mm, the surface is soft and the anti-blocking agent sinks into the resin, resulting in poor slipperiness and anti-blocking properties. 2 To achieve a Martens hardness of 0.5% or less, it is preferable to use polypropylene copolymerized with 0.5% or less ethylene and / or an α-olefin having 4 or more carbon atoms, more preferably 0.1% or less, and most preferably a completely homopolypropylene containing no copolymerization components. It is also possible to increase the Martens hardness by setting the mesopentad fraction ([mmmm]%) of the constituent polypropylene to 98% or more and increasing the degree of crystallinity. The Martens hardness of the surface layer (C) of the polypropylene-based laminated film is 350N / mm 2 It is preferable that:

[0038] The polypropylene resin used in the present invention is obtained by polymerizing the raw material propylene using a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst. Among them, it is preferable to use a Ziegler-Natta catalyst in order to eliminate heterogeneous bonds, and to use a catalyst capable of polymerization with high stereoregularity. As a method for polymerizing the raw material propylene, a known method may be adopted, and examples thereof include a method of polymerizing in an inert solvent such as hexane, heptane, toluene, or xylene, a method of polymerizing in a liquid monomer, a method of adding a catalyst to a gaseous monomer and polymerizing in a gas phase state, or a method of polymerizing by combining these methods.

[0039] The base layer (A) and / or the surface layer (B) and / or the surface layer (C) of the polypropylene-based laminate film of the present invention may contain additives or other resins. Examples of additives include antioxidants, ultraviolet absorbers, nucleating agents, adhesives, antifogging agents, flame retardants, inorganic or organic fillers, etc. Examples of other resins include polypropylene resins other than the polypropylene resin used in the present invention, random copolymers which are copolymers of propylene and ethylene and / or α-olefins having 4 or more carbon atoms, and various elastomers. These may be sequentially polymerized using a multi-stage reactor, blended with a polypropylene resin in a Henschel mixer, master pellets prepared in advance using a melt kneader may be diluted with polypropylene to a predetermined concentration, or the entire amount may be melt kneaded in advance before use. Furthermore, corona discharge treatment, glow discharge treatment, flame treatment, surface roughening treatment, and known anchor coat treatment, printing, decoration, etc. may be performed as long as they do not impair the object of the present invention.

[0040] (3) Polypropylene laminate film The polypropylene-based laminate film of the present invention is preferably a biaxially oriented film and has a three-layer structure of surface layer (B) / base layer (A) / surface layer (C). However, it may also have a two-layer structure of surface layer (B) / base layer (A), a four-layer structure of surface layer (B) / base layer (A) / intermediate layer (D) / surface layer (C), or a multilayer structure with more than one layer. When there are a plurality of base layers (A), surface layers (B) and surface layers (C), the compositions of the layers may be different as long as each layer satisfies the required characteristics.

[0041] The overall thickness of the polypropylene-based laminate film of the present invention is preferably 9 μm or more and 200 μm or less, more preferably 10 μm or more and 150 μm or less, further preferably 12 μm or more and 100 μm or less, and particularly preferably 15 μm or more and 80 μm or less.

[0042] In the polypropylene-based laminate film of the present invention, the ratio of the thickness of the surface layer (B) to the thickness of the base layer (A) is preferably 0.01 to 0.50, more preferably 0.02 to 0.40, even more preferably 0.03 to 0.30, and particularly preferably 0.04 to 0.20. If the ratio of the thickness of the surface layer (B) to the thickness of the base layer (A) exceeds 0.50, the heat shrinkage tends to increase.

[0043] In addition, the ratio of the thickness of the surface layer (C) to the thickness of the base layer (A) in the polypropylene-based laminate film is preferably 0.01 to 0.50, more preferably 0.02 to 0.40, even more preferably 0.03 to 0.30, and particularly preferably 0.04 to 0.20. If the ratio of the surface layer (C) to the base layer (A) exceeds 0.50, the haze increases and the transparency deteriorates depending on the amount of the antiblocking agent added.

[0044] The thickness of the entire base layer (A) relative to the thickness of the entire film is preferably 50% or more and 99% or less, more preferably 60% or more and 97% or less, particularly preferably 70% or more and 95% or less, and most preferably 80% or more and 92% or less.

[0045] The haze of the polypropylene laminate film of the present invention is preferably 5% or less, regardless of the presence or absence of an inorganic thin film (D), more preferably 0.2 to 5.0%, even more preferably 0.3 to 4.5%, and particularly preferably 0.4 to 4.0%. When the haze is within the above range, it may be easy to use in applications where transparency is required. For example, the haze tends to deteriorate when the stretching temperature or heat setting temperature is too high, the cooling roll temperature is high and the cooling rate of the unstretched (raw) sheet is slow, or there is too much low molecular weight component, and it can be adjusted to the above range. The method for measuring the haze will be described later.

[0046] The tensile modulus in the longitudinal direction (MD direction) of the polypropylene-based laminated film of the present invention is preferably 1.8 GPa or more and 4.0 GPa or less, more preferably 2.0 GPa or more and 3.7 GPa or less, even more preferably 2.1 GPa or more and 3.5 GPa or less, and particularly preferably 2.2 GPa or more and 3.4 GPa or less. The tensile modulus in the transverse direction (TD direction) is preferably 3.8 GPa or more and 8.0 GPa or less, more preferably 4.0 GPa or more and 7.5 GPa or less, even more preferably 4.1 GPa or more and 7.0 GPa or less, and particularly preferably 4.2 GPa or more and 6.5 GPa or less. If the tensile modulus is within the above range, the film will have a strong elasticity and can be used even with a small film thickness, so that the amount of film used can be reduced. The method for measuring the tensile modulus will be described later.

[0047] In the polypropylene laminated film of the present invention, the longitudinal heat shrinkage at 150°C is preferably 0.2% or more and 15.0% or less, more preferably 0.3% or more and 13.0% or less, even more preferably 0.5% or more and 11.0% or less, and particularly preferably 0.5% or more and 9.0% or less. If the heat shrinkage is within the above range, the film can be said to have excellent heat resistance and can be used in applications where it may be exposed to high temperatures. Note that the 150°C heat shrinkage can be reduced to about 1.5% by, for example, increasing the amount of low molecular weight components or adjusting the stretching conditions and heat fixing conditions, but to reduce it below that, it is preferable to perform offline annealing treatment, etc. In the polypropylene laminated film of the present invention, the transverse heat shrinkage at 150°C is preferably 0.5% or more and 30.0% or less, more preferably 0.5% or more and 25.0% or less, even more preferably 0.5% or more and 20.0% or less, and particularly preferably 0.5% or more and 18.0% or less. If the heat shrinkage is within the above range, the film can be said to have excellent heat resistance and can be used in applications where it may be exposed to high temperatures. Note that the 150°C heat shrinkage can be reduced to about 1.5% by, for example, increasing the amount of low molecular weight components or adjusting the stretching conditions and heat setting conditions, but to reduce it below that, it is preferable to perform offline annealing treatment, etc.

[0048] The dynamic friction coefficient of the surface layer (B) and the surface layer (C) of the polypropylene-based laminate film of the present invention is preferably 0.60 or less, more preferably 0.55 or less, and particularly preferably 0.50 or less. When the dynamic friction coefficient is 0.60 or less, the film can be smoothly unwound from the roll film, and printing processing is easy.

[0049] The air escape time between the surface layer (B) and the surface layer (C) of the polypropylene-based laminate film of the present invention is preferably 10 seconds or less, more preferably 8 seconds or less, and even more preferably 5 seconds or less. If the air escape time exceeds 10 seconds, the air escapes slowly when the film is rolled up, and wrinkles are likely to occur.

[0050] (4) Manufacturing method The polypropylene-based laminated film of the present invention is preferably a biaxially oriented film, and can be obtained by melt-extruding the polypropylene-based resin composition constituting the base layer (A), the polypropylene-based resin composition constituting the surface layer (B), and the polypropylene-based resin composition constituting the surface layer (C) using separate extruders, co-extruding from a die, and cooling with a cooling roll to form an unstretched sheet, stretching the unstretched sheet in the machine direction (MD) and the transverse direction (TD), and then heat-setting the sheet. It is preferable to extrude the surface layer (B) so that the surface layer (B) is in contact with the cooling roll. If the surface layer (B) is on the opposite side to the surface that is in contact with the cooling roll, the polypropylene resin is slowly cooled, the crystallization degree is increased, and the arithmetic average roughness (Ra) of the surface of the surface layer (B) may be too large due to surface unevenness caused by spherulites. The melt extrusion temperature is preferably about 200 to 280°C. In order to obtain a laminated film with good appearance without disturbing the layers within this temperature range, it is preferable that the viscosity difference (MFR difference) between the polypropylene raw material for the base layer (A) and the polypropylene raw material for the surface layer (B) is 6.0 g / 10 min or less. If the viscosity difference is more than 6 g / 10 min, the layers are likely to be disturbed, resulting in poor appearance. The viscosity difference is more preferably 5.5 g / 10 min or less, and even more preferably 5.0 g / 10 min or less.

[0051] The surface temperature of the cooling roll is preferably 25 to 35° C., more preferably 27 to 33° C. If the cooling roll temperature exceeds 35° C., the degree of crystallinity of the polypropylene resin increases, and the arithmetic mean roughness (Ra) of the surface of the surface layer (B) may become too large due to surface irregularities caused by the formed spherulites.

[0052] The lower limit of the stretching ratio in the machine direction (MD) is preferably 3 times, more preferably 3.5 times. If it is less than the above, the film thickness may become uneven. The upper limit of the stretching ratio in the MD is preferably 8 times, more preferably 7 times. If it exceeds the above, the subsequent TD stretching may become difficult. The lower limit of the MD stretching temperature is preferably 120 ° C, more preferably 125 ° C, and even more preferably 130 ° C. If it is less than the above, the mechanical load may become large, the thickness unevenness may become large, and the surface of the film may become rough. The upper limit of the MD stretching temperature is preferably 160 ° C, more preferably 155 ° C, and even more preferably 150 ° C. A higher temperature is preferable for reducing the heat shrinkage rate, but it may adhere to the roll, making it impossible to stretch, or the surface may become rough.

[0053] The lower limit of the stretching ratio in the transverse direction (TD) is preferably 4 times, more preferably 5 times, and even more preferably 6 times. If it is less than the above, thickness unevenness may occur. The upper limit of the TD stretching ratio is preferably 20 times, more preferably 17 times, even more preferably 15 times, and particularly preferably 12 times. If it exceeds the above, the heat shrinkage rate may increase or the film may break during stretching. The preheating temperature in TD stretching is preferably set to be 5 to 15°C higher than the stretching temperature in order to quickly raise the film temperature to the vicinity of the stretching temperature. The lower limit of the TD stretching temperature is preferably 150°C, more preferably 155°C, even more preferably 158°C, and especially preferably 160°C. If it is less than the above, the film may break due to insufficient softening, or the heat shrinkage rate may increase. The upper limit of the TD stretching temperature is preferably 170°C, more preferably 168°C, and even more preferably 165°C. To reduce the heat shrinkage rate, a higher temperature is preferable, but if the temperature exceeds the above range, the low molecular weight components will melt and recrystallize, causing not only a decrease in orientation but also surface roughness and whitening of the film.

[0054] The stretched film is heat set. The lower limit of the heat setting temperature is preferably 163°C, more preferably 165°C. If the temperature is lower than the above, the heat shrinkage rate may be high. In addition, a long period of treatment may be required to reduce the heat shrinkage rate, which may result in poor productivity. The upper limit of the heat setting temperature is preferably 176°C, more preferably 175°C. If the temperature exceeds the above range, low molecular weight components may melt and recrystallize, causing surface roughness and whitening of the film.

[0055] It is preferable to relax the film during heat setting. The lower limit of the relaxation rate is preferably 2%, more preferably 3%. If it is less than the above, the thermal shrinkage rate may be high. The upper limit of the relaxation rate is preferably 10%, more preferably 8%. If it exceeds the above, the thickness unevenness may become large.

[0056] Furthermore, in order to reduce the thermal shrinkage rate, the film produced by the above process may be wound into a roll and then annealed offline.

[0057] The biaxially oriented polypropylene laminate film thus obtained can be subjected to corona discharge, plasma treatment, flame treatment, etc., as necessary, and then wound up with a winder to obtain the biaxially oriented polypropylene film roll of the present invention.

[0058] [Inorganic thin film layer] The gas barrier laminated film of the present invention has an inorganic thin film layer on the surface of the base film layer. The inorganic thin film layer is a thin film made of a metal or an inorganic oxide. There is no particular limitation on the material forming the inorganic thin film layer as long as it can be made into a thin film, but from the viewpoint of gas barrier properties, inorganic oxides such as silicon oxide (silica), aluminum oxide (alumina), and a mixture of silicon oxide and aluminum oxide are preferred. In this composite oxide, the mixing ratio of silicon oxide and aluminum oxide is preferably in the range of 20 to 70 mass% of Al in terms of the mass ratio of the metal content. If the Al concentration is less than 20 mass%, the water vapor barrier properties may be reduced. On the other hand, if it exceeds 70 mass%, the inorganic thin film layer tends to become hard, and the film may be destroyed during secondary processing such as printing or lamination, resulting in a decrease in gas barrier properties. In addition, when the Al concentration is 100 mass%, the water vapor barrier performance is good, but since it is a single material, the surface tends to be smooth, and the slipperiness is poor, making it easy for processing defects (wrinkles, acne, etc.) to occur. The silicon oxide referred to here is various silicon oxides such as SiO and SiO2, or mixtures thereof, and the aluminum oxide is various aluminum oxides such as AlO and Al2O3, or mixtures thereof.

[0059] The inorganic thin film layer has a thickness of usually 1 to 100 nm, preferably 5 to 50 nm. If the inorganic thin film layer has a thickness of less than 1 nm, it may be difficult to obtain satisfactory gas barrier properties, while if the inorganic thin film layer has a thickness exceeding 100 nm, the corresponding improvement in gas barrier properties cannot be obtained, and it is rather disadvantageous in terms of flex resistance and production costs.

[0060] The method for forming the inorganic thin film layer is not particularly limited, and any known deposition method, such as physical deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, or chemical deposition (CVD), may be appropriately adopted. A typical method for forming the inorganic thin film layer will be described below using a silicon oxide / aluminum oxide thin film as an example. For example, when the vacuum deposition method is adopted, a mixture of SiO2 and Al2O3, or a mixture of SiO2 and Al, is preferably used as the deposition raw material. Particles are usually used as these deposition raw materials, and in this case, it is desirable that the size of each particle is large enough that the pressure during deposition does not change, and the preferred particle diameter is 1 mm to 5 mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, or other methods. It is also possible to introduce oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, or other reactive gases as reaction gases, or to adopt reactive deposition using means such as ozone addition and ion assist. Furthermore, the film formation conditions can be changed arbitrarily, such as applying a bias to the deposition target (laminated film to be subjected to deposition), or heating or cooling the deposition target. The deposition material, reaction gas, bias of the deposition target, heating / cooling, etc. can be changed in the same manner when the sputtering method or the CVD method is adopted.

[0061] The laminated film of the present invention must have a water contact angle of 75° or less on the surface of the inorganic thin film layer (D). It is preferably 10° or more and 70° or less, more preferably 15° or more and 65° or less, and even more preferably 20° or more and 60° or less. The water contact angle is an index representing the film quality of the inorganic thin film layer. By setting the water contact angle within the above range, it is possible to obtain water-resistant adhesion and good barrier performance. If the water contact angle is less than 10°, the film is hydrophilized, so there is a risk of the water vapor barrier property being deteriorated. Furthermore, since the adhesion to the substrate is deteriorated due to the hydrophilic surface, water is likely to penetrate between the layers, and the water-resistant adhesion tends to decrease. On the other hand, if the water contact angle is greater than 75°, it cannot be said that the inorganic film is formed uniformly, and the barrier performance is deteriorated.

[0062] The value of the water contact angle of the inorganic thin film layer (D) surface depends on the material used for the inorganic thin film layer. Regarding the material, the aluminum or aluminum oxide concentration in the inorganic thin film layer (D) is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more. If the aluminum oxide concentration is less than 30% by mass, the film becomes hydrophilic, and the water contact angle mentioned above becomes equal to or less than the lower limit.

[0063] The present inventors have found that the water contact angle of the inorganic thin film layer (D) surface also depends on the surface resistance of the substrate (degree of exposure of the antistatic agent). The antistatic agent has a hydrophilic site such as a hydrophilic group for exerting an antistatic effect, and it was predicted that when the antistatic agent is exposed (bleeds out) to the surface layer (B), the water contact angle of the inorganic thin film layer (D) surface would be smaller than that of the case where the antistatic agent is not contained. However, it was found that the exposure of the antistatic agent increases the water contact angle of the inorganic thin film layer (D) surface. The surface resistance of the surface of the surface layer (B) of the substrate film in the present invention is preferably 14 Log Ω or more. When the surface resistance is 14 Log Ω or more, the exposure of the antistatic agent that inhibits the lamination of the inorganic thin film layer (D) is small, so that the inorganic thin film layer can be laminated uniformly and the barrier property is improved. In this case, the water contact angle of the inorganic thin film layer (D) is within a predetermined range. The surface resistance is more preferably 15 Log Ω or more, and particularly preferably 16 Log Ω or more. If the surface resistance is less than 14 Log Ω, the antistatic agent that bleeds into the surface layer (B) will hinder the lamination of the inorganic thin film layer (D), resulting in an uneven film. In that case, the water contact angle may be affected by the underlying substrate surface and exceed the upper limit. In order to achieve a surface resistance of 14 Log Ω or more, it is recommended to avoid using additives such as antistatic agents and antifogging agents as much as possible. Also, care must be taken because additives contained in the substrate layer (A) may bleed onto the surface of the surface layer (B).

[0064] Furthermore, the water contact angle of the inorganic thin film layer (D) surface is also affected by the minute unevenness of the surface. The contact angle can be finely adjusted by controlling the arithmetic mean roughness (Ra) of the inorganic thin film layer (D) side of the laminated film (described later) by scanning probe microscope (AFM) within a specified range.

[0065] The laminated film of the present invention is preferably such that the arithmetic mean roughness (Ra) of the surface on the inorganic thin film layer (D) side measured by a scanning probe microscope (AFM) is 4.5 nm or more and 9.0 nm or less. The arithmetic mean roughness Ra has almost the same tendency as the roughness of the surface layer (B) of the above-mentioned substrate film, but the inventors have found that the roughness further changes after the formation of the inorganic thin film layer. The reason for this is not clear, but it is believed that the unevenness of the substrate resin changes due to the application of heat to the film during the inorganic thin film lamination process, and further additives such as low molecular weight components and antistatic agents are exposed from the substrate, which affects the unevenness state. If the arithmetic mean roughness (Ra) is within the above range, not only is the adhesion between the inorganic thin film layer and the substrate improved, but by forming larger surface unevenness, the adhesiveness when a protective layer, adhesive, printing layer, etc. are further laminated can be maintained. If the arithmetic mean roughness (Ra) is less than 4.5 nm, the surface area is small and the adhesion strength is reduced. If the arithmetic mean roughness (Ra) exceeds 9.0 nm, the surface will be uneven and non-uniform, which may result in reduced adhesion. The arithmetic mean roughness (Ra) of the inorganic thin film layer (D) side surface is more preferably 4.7 nm or more, even more preferably 4.9 nm or more, particularly preferably 5.1 nm or more, and most preferably 5.3 nm or more. In order to set the arithmetic mean roughness (Ra) of the surface on the inorganic thin film layer (D) side to 4.5 nm or more and 9.0 nm or less, in addition to setting the arithmetic mean roughness (Ra) of the surface layer (B) of the substrate film in the preferred range described above, adjustments can be made by changing the presence or absence of additives derived from the substrate, the film cooling conditions during the inorganic thin film formation process, the thin film material, composition, film thickness, etc. [Protective layer] In the present invention, when gas barrier performance is required or processing such as printing is required, a protective layer can be provided on the inorganic thin film layer (D). The inorganic thin film layer is not a completely dense film, but has minute defects scattered therein. By forming a protective layer by applying a specific resin composition for protective layer described later on the inorganic thin film layer, the resin in the resin composition for protective layer penetrates into the defective parts of the inorganic thin film layer, resulting in an effect of stabilizing the gas barrier property. In addition, by using a material having gas barrier property for the protective layer itself, the gas barrier property of the laminated film is also greatly improved. However, it is necessary to note that the provision of the protective layer increases the number of processes, which increases the cost, and that depending on the material used, it may cause a burden on the environment. It is also necessary to note that the physical properties such as surface roughness change depending on the protective layer.

[0066] The amount of protective layer attached is 0.10 to 1.00 (g / m 2 ) is preferable. This allows the protective layer to be uniformly controlled during coating, resulting in a film with fewer coating irregularities and defects. In addition, the cohesive force of the protective layer itself is improved, and the adhesion between the inorganic thin film layer and the protective layer is also strengthened. The coating weight of the protective layer is preferably 0.13 (g / m 2 ) or more, more preferably 0.16 (g / m 2 ) or more, and more preferably 0.19 (g / m 2 ) or more, and preferably 0.0.97 (g / m 2 ) or less, more preferably 0.94 (g / m 2 ) or less, more preferably 0.91 (g / m 2 ) or less. The adhesion weight of the protective layer is 1.00 (g / m 2 ), the gas barrier properties improve, but the cohesive force inside the protective layer becomes insufficient and the uniformity of the protective layer also decreases, resulting in unevenness or defects in the coat appearance and inability to fully demonstrate gas barrier properties and adhesiveness. On the other hand, if the thickness of the protective layer exceeds 0.10 (g / m 2 ) there is a risk that sufficient gas barrier properties and interlayer adhesion cannot be obtained.

[0067] Resin compositions used for the protective layer formed on the surface of the inorganic thin film layer (D) of the laminate film of the present invention include resins such as vinyl alcohol-based, urethane-based, polyester-based, acrylic-based, titanium-based, isocyanate-based, imine-based, and polybutadiene-based resins to which curing agents such as epoxy-based, isocyanate-based, and melamine-based curing agents have been added.

[0068] The method of coating the resin composition for the protective layer is not particularly limited as long as it is a method that coats the film surface to form a layer. For example, a typical coating method such as gravure coating, reverse roll coating, wire bar coating, or die coating can be used.

[0069] When forming a protective layer, it is preferable to apply the resin composition for the protective layer and then heat-dry it. The drying temperature is preferably 100 to 160°C, more preferably 105 to 155°C, and even more preferably 110 to 150°C. If the drying temperature is less than 100°C, the protective layer may be insufficiently dried, or the film formation of the protective layer may not proceed, resulting in a decrease in cohesive strength and water-resistant adhesion, and as a result, the barrier properties and hand-tearability may decrease. On the other hand, if the drying temperature exceeds 160°C, the film may be too hot, making it brittle and reducing the puncture strength, or shrinking and causing poor processability. In particular, by drying at 100°C or higher, preferably 110°C or higher, the film formation of the protective layer progresses effectively, and the adhesive area between the resin of the protective layer and the inorganic thin film layer becomes larger, thereby improving the water-resistant adhesion. It is particularly preferable to first volatilize the solvent at a relatively low temperature of about 90°C immediately after application, and then dry at 100°C or higher, since a uniform film can be obtained. In addition to drying, additional heat treatment at a temperature as low as possible is also effective in accelerating the formation of the protective layer.

[0070] [Packaging materials] When the laminated film of the present invention is used as a packaging material, it is preferable to form a laminate having a heat-sealable resin layer called a sealant. The heat-sealable resin layer is usually provided on the inorganic thin film layer, but may also be provided on the outside of the base film layer (the surface opposite to the surface on which the inorganic thin film is formed). The heat-sealable resin layer is usually formed by extrusion lamination or dry lamination. The thermoplastic polymer forming the heat-sealable resin layer may be any polymer capable of sufficiently exhibiting sealant adhesion, and may be, for example, polyethylene resins such as olefin-based HDPE, LDPE, and LLDPE, polypropylene resins, ethylene-vinyl acetate copolymers, ethylene-α-olefin random copolymers, and ionomer resins. Among these, LLDPE or polypropylene resins, which are highly versatile in terms of durability, seal strength, cost, and mono-materialization, are particularly preferable. The thickness of the sealant layer is preferably 20 to 100 μm, more preferably 30 to 90 μm, and even more preferably 40 to 80 μm. If the thickness is less than 20 μm, sufficient seal strength may not be obtained, or the sealant may lack stiffness and be difficult to handle. On the other hand, if the thickness exceeds 100 μm, the bag will feel stiff and will be difficult to handle, and the price may also become high.

[0071] [Adhesive layer] The adhesive layer used in the present invention can be a general-purpose adhesive for lamination. For example, (non-)solvent, water-based, or hot melt adhesives mainly composed of poly(ester)urethane, polyester, polyamide, epoxy, poly(meth)acrylic, polyethyleneimine, ethylene-(meth)acrylic acid, polyvinyl acetate, (modified) polyolefin, polybutadiene, wax, or casein can be used. Among these, urethane or polyester adhesives are preferred in consideration of heat resistance and flexibility that can follow the dimensional changes of each substrate. The adhesive layer can be laminated by, for example, direct gravure coating, reverse gravure coating, kiss coating, die coating, roll coating, dip coating, knife coating, spray coating, fountain coating, or other methods, and the coating amount after drying is preferably 1 to 8 g / m2 in order to develop sufficient adhesiveness. More preferably, it is 2 to 7 g / m2. 2 , and more preferably 3 to 6 g / m 2 The coating amount is 1g / m 2 If it is less than 8g / m, it becomes difficult to bond the entire surface, and the adhesive strength decreases. 2 If the temperature exceeds this range, it will take a long time for the film to completely cure, unreacted material will be likely to remain, and adhesive strength will decrease.

[0072] Furthermore, in the laminate film of the present invention, at least one printed layer or other plastic substrate and / or paper substrate may be laminated between the substrate film layer and the heat-sealable resin layer or on the outer side thereof.

[0073] As the printing ink for forming the printing layer, water-based and solvent-based resin-containing printing inks can be preferably used. Examples of the resin used in the printing ink include acrylic resins, urethane resins, polyester resins, vinyl chloride resins, vinyl acetate copolymer resins, and mixtures thereof. The printing ink may contain known additives such as antistatic agents, light blocking agents, ultraviolet absorbers, plasticizers, lubricants, fillers, colorants, stabilizers, lubricants, defoamers, crosslinking agents, anti-blocking agents, and antioxidants. The printing method for providing the printing layer is not particularly limited, and known printing methods such as offset printing, gravure printing, and screen printing can be used. To dry the solvent after printing, known drying methods such as hot air drying, hot roll drying, and infrared drying can be used.

[0074] The laminated film of the present invention has an oxygen permeability of 60 cc / m under conditions of 23°C x 65% RH. 2 It is preferable that the viscosity is 50 cc / m or less in order to exhibit good gas barrier properties. 2 ·d·atm or less, preferably 40cc / m 2 ·d·atm or less. Oxygen permeability is 60cc / m 2 If the oxygen permeability exceeds 0.1cc / m, it becomes difficult to meet the requirements for high gas barrier properties. 2 If the oxygen permeability is less than 0.1 cc / m, the barrier performance is excellent, but the residual solvent is less likely to permeate to the outside of the bag, and the amount of the solvent that migrates to the contents is relatively increased, which is undesirable. The preferable lower limit of the oxygen permeability is 0.1 cc / m 2 ·d·atm or higher.

[0075] The laminate of the present invention has a water vapor permeability of 4.0 g / m under conditions of 40°C x 90% RH. 2 In terms of exhibiting good gas barrier properties, it is preferable that the thickness is 3.5 g / m or less. 2 d or less, preferably 3.0 g / m 2 ·d or less. The water vapor permeability is 4.0g / m 2If the water vapor permeability exceeds 0.1 g / m, it becomes difficult to meet the requirements for applications that require high gas barrier properties. 2 If the water vapor permeability is less than 0.1 g / m, the barrier performance is excellent, but the residual solvent is less likely to permeate to the outside of the bag, and the amount of the solvent that migrates to the contents may increase relatively, which is not preferable. 2 ·d or more.

[0076] When the oxygen permeability value of the laminated film of the present invention measured under conditions of 23°C x 65% RH is (A) and the oxygen permeability value measured under conditions of 23°C x 80% RH is (B), the barrier value deterioration rate under high temperature and high humidity conditions represented by the following formula is preferably 130% or less, more preferably 125% or less, and even more preferably 120% or less. If the deterioration rate is more than 130%, there is a risk that the barrier performance will deteriorate under high humidity, which is not preferable because the use environment and applications will be limited. Barrier value deterioration rate under high temperature and humidity conditions (%) = (B / A) x 100 (Formula 1)

[0077] The laminate of the present invention preferably has a laminate strength of 1.5 N / 15 mm or more under conditions of 23°C x 65% RH, more preferably 2.0 N / 15 mm or more, and even more preferably 2.5 N / 15 mm or more. If the laminate strength is less than 1.5 N / 15 mm, peeling may occur due to bending load or heat during sealing, resulting in deterioration of barrier properties or leakage of contents. Furthermore, there is a risk of deterioration in tearability by hand. EXAMPLES

[0078] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples. The films were evaluated by the following measurement methods.

[0079] [Physical properties of base film] (1) Mesopentad fraction ([mmmm] unit: %) The mesopentad fraction was measured using 13C-NMR. The mesopentad fraction was calculated according to the method described in "Zambelli et al., Macromolecules, Vol. 6, p. 925 (1973)". 13C-NMR measurements were performed at 110°C using BRUKER's "AVANCE500" by dissolving 200 mg of a sample in a mixture of o-dichlorobenzene and heavy benzene at a volume ratio of 8:2 at 135°C.

[0080] (2) Melt flow rate ([MFR]g / 10 min) The measurements were performed in accordance with JIS K7210 at a temperature of 230°C and a load of 2.16 kgf. In the case of raw resin, the pellets (powder) were weighed out and used in the required amount. In the case of film, the required amount was cut out and then cut into samples of approximately 5 mm square.

[0081] (3) Molecular weight and molecular weight distribution The molecular weight and molecular weight distribution of the raw material resin and the film were determined by gel permeation chromatography (GPC) using monodisperse polystyrene as a standard. The measurement conditions such as the column and solvent used in the GPC measurement are as follows: Solvent: 1,2,4-trichlorobenzene Column: TSKgel GMHHR-H(20)HT x 3 Flow rate: 1.0ml / min Detector: RI Measurement temperature: 140℃

[0082] The number average molecular weight (Mn), mass average molecular weight (Mw), and molecular weight distribution (Mw / Mn) are each defined by the number of molecules (Ni) of the molecular weight (Mi) at each elution position of the GPC curve obtained via the molecular weight calibration curve, as shown in the following equations. Number average molecular weight: Mn=Σ(Ni·Mi) / ΣNi Mass average molecular weight: Mw=Σ(Ni·Mi 2 ) / Σ(Ni·Mi) Molecular weight distribution: Mw / Mn When the baseline was unclear, the baseline was set in the range up to the lowest position of the high molecular weight side tail of the elution peak on the high molecular weight side closest to the elution peak of the standard substance.

[0083] (4) Melting peak temperature (℃), melting peak area (J / g) Using a differential scanning calorimeter (DSC) manufactured by SII, measurements were performed with a sample weight of 10 mg and a heating rate of 20° C. / min. The melting endothermic peak temperature and melting peak area were determined from the DSC curve.

[0084] (5) Thickness (μm) The thickness of each of the base layer (A) and surface layer (B) was measured by cutting a cross section of a biaxially oriented laminated polypropylene film solidified with a modified urethane resin using a microtome and observing it with a differential interference microscope.

[0085] (6) Tensile modulus (GPa) Measurements were performed according to JIS K 7127. A sample with a width of 10 mm and a length of 180 mm was cut out using a razor in the longitudinal and transverse directions of the film. After leaving the film for 12 hours in an atmosphere of 23°C and 65% RH, measurements were performed under conditions of 23°C, 65% RH, chuck distance of 100 mm, and pulling speed of 200 mm / min, and the average value of five measurement results was used. The measurement device used was an autograph AG5000A manufactured by Shimadzu Corporation.

[0086] (7) Heat shrinkage rate (%) The measurement was performed according to the following method in accordance with JIS Z1712. The film was cut to a width of 20 mm and a length of 200 mm in each of the MD and TD directions, and was hung in a hot air oven at 150°C and heated for 5 minutes. The length before and after heating was measured, and the ratio (%) of the length before heating minus the length after heating to the length before heating was calculated to determine the thermal shrinkage rate.

[0087] (8) Wetting tension (mN / m) In accordance with K 6768:1999, the film was aged at 23°C and 50% relative humidity for 24 hours, and then the corona-treated surface of the film was measured using the following procedure. Step 1) The measurements shall be carried out in a standard laboratory atmosphere (see JIS K 7100) with a temperature of 23°C and a relative humidity of 50%. Step 2) The test specimen is placed on the substrate of the hand coater (4.1), a few drops of the test mixture are placed on the specimen, and immediately spread by pulling the wire bar. If a cotton swab or brush is used to spread the test mixture, the liquid should be spread quickly over an area of ​​at least 6 cm2, with just enough liquid to form a thin layer without pooling. The wetting tension is judged by observing the liquid film of the test mixture in a bright place and the state of the liquid film after 3 seconds. If the liquid film does not break and the state at the time of application is maintained for 3 seconds or more, it is considered to be wet. If the wetness is maintained for 3 seconds or more, proceed to the mixed liquid with the next higher surface tension, and conversely, if the liquid film breaks in 3 seconds or less, proceed to the mixed liquid with the next lower surface tension. Repeat this process to select the mixture that can accurately wet the surface of the test piece within 3 seconds. Step 3) Use a new swab for each test. Brushes or wire bars should be cleaned with methanol and dried after each use, as residual liquid will change composition and surface tension upon evaporation. Step 4) The procedure is repeated at least three times to select the mixture that can wet the surface of the test piece in 3 seconds, and the surface tension of the mixture thus selected is reported as the wetting tension of the film.

[0088] (9) Surface resistance value (LogΩ) According to JIS K6911, the film was aged at 23° C. for 24 hours, and then the surface resistance of the surface layer (B) of the film was measured.

[0089] (10) Air release time (seconds) As shown in Figure 1, film 4 is placed on base plate 1. Next, film holder 2 is placed on top of film 4 and fixed in place to apply tension to film 4. Next, film 5 is placed on top of film holder 2 with the side opposite to the top surface of film 4 placed on base plate 1 facing down. Next, film holder 8 is placed on top of film 5, and the film holders 8, 2 and base plate 1 are fixed in place using screws 3. Next, cavity 2a in film holder 2 is connected to vacuum pump 6 via small hole 2c in film holder 2 and pipe 7. When vacuum pump 6 is driven, film 5 is sucked into cavity 2a and tension is applied to it. At the same time, the pressure in the overlapping surfaces of films 4 and 5 is reduced via small hole 2d provided circumferentially in film holder 2, and films 4 and 5 begin to adhere to each other from the outer periphery at their overlapping surfaces. The state of adhesion can be easily confirmed by observing the interference fringes from above the overlapping surfaces. Then, the time (seconds) from when interference fringes appear on the outer periphery of the overlapping surfaces of films 4 and 5 until they spread to the front of the overlapping surfaces and stop moving is measured, and this time (seconds) is the air release time. The measurement is repeated five times by replacing the two films, and the average value is used. In other words, the shorter the time (seconds), the better the film winding characteristics.

[0090] (11) Roll wrinkle evaluation The formed substrate film was wound up to a width of 500 mm and a length of 1000 m, and the wrinkles on the surface layer of the roll were visually evaluated according to the following criteria. ○: No wrinkles △: There are slight wrinkles, but the wrinkles disappear when a tension of about 20 N / m is applied to the pulled-out film. ×: There are strong wrinkles, and the wrinkles do not disappear even when a tension of about 20 N / m is applied to the pulled-out film.

[0091] [Physical properties of laminated film after lamination of inorganic thin film] (12) Haze (%) Measurement was performed at 23° C. in accordance with JIS K 7105. Measurement was performed using a haze meter (300A, manufactured by Nippon Denshoku Industries Co., Ltd.) The measurement was performed twice, and the average value was calculated.

[0092] (13) Composition and thickness of inorganic thin film layer The film thickness composition of the laminated films (after thin film lamination) obtained in the examples and comparative examples was measured using a fluorescent X-ray analyzer ("ZSX100e" manufactured by Rigaku Corporation) based on a calibration curve prepared in advance. The excitation X-ray tube conditions were 50 kV and 70 mA.

[0093] (14) Martens hardness (N / mm 2 ) The obtained laminated film was cut into approximately 2 cm squares, and the surface opposite to the measurement surface was fixed with an adhesive on a glass plate with a thickness of approximately 1 mm, and then the plate was left for 12 hours in an atmosphere of 23°C and 50% RH to condition the humidity. This sample was measured using a dynamic ultra-microhardness tester (Shimadzu Corporation's "DUH-211") under the following measurement conditions according to the method of ISO14577-1 (2002). The measurement was performed 10 times by changing the position of the film, and the average value of 8 points excluding the maximum and minimum was calculated.

[0094] <Measurement conditions> (setting) Measurement environment: Temperature 23°C, relative humidity 50% Test mode: Load-unload test ·Indenter used: ridge angle 115 degrees, triangular pyramid indenter Indentation modulus: 1.140×106N / mm2 Indenter Poisson's ratio: 0.07 Cf-Ap,As correction: Yes (conditions) Test force: 0.10mN ·Load speed: 0.0050mN / sec ·Load holding time: 5sec ·Unloading holding time: 0sec

[0095] (15) Center surface average roughness ([SRa]μm) The center surface average roughness (SRa) of the obtained laminated film was measured using a three-dimensional roughness meter (manufactured by Kosaka Laboratory, model number ET-30HK) with a stylus pressure of 20 mg, a measurement length in the X direction of 1 mm, a feed speed of 100 μm / sec, a feed pitch in the Y direction of 2 μm, 99 recorded lines, a height direction magnification of 20,000 times, and a cutoff of 80 μm, and calculated in accordance with the definition of arithmetic average roughness described in JIS-B0601 (1994). The arithmetic mean roughness (SRa) was evaluated by averaging three trials each.

[0096] (16) Arithmetic mean roughness ([Ra] nm) The arithmetic mean roughness (Ra) of the obtained laminated film was measured using a scanning probe microscope (Shimadzu Corporation, "SPM-9700") in dynamic mode. Measurements were performed in the range of 2 μm in both the X and Y directions, and the obtained images were corrected (tilt, line fit, noise line removal), and then the arithmetic mean roughness was calculated according to the definition of JIS-B0601 (1994).

[0097] (17) Water contact angle of inorganic thin film layer (D) For the laminated films (after lamination of inorganic thin film) obtained in the examples and comparative examples, water was dropped onto the film using a contact angle meter (model: CAM200, sold by Altec Alto Co., Ltd., manufactured by KSV Instruments, Finland), and the contact angle was measured. The contact angle was read 5 seconds after the water was dropped onto the film. FAMAS (Kyowa Interface Science Co., Ltd.) was used as the analysis software. Detailed measurement conditions are shown below. Temperature and humidity: 23℃, 65% Measurement method: Droplet method (θ / 2 method) Droplet size: 7.0μL Needle size: 22G, inner diameter 0.4mm

[0098] (18) Evaluation method for oxygen permeability In each example and comparative example, the laminated film obtained at the stage of laminating the inorganic thin film layer (D) on the substrate film and the laminated body described below were used as samples, and the oxygen permeability was measured in an atmosphere at a temperature of 23° C. and a humidity of 65% RH or 80% RH using an oxygen permeability measuring device ("OX-TRAN (registered trademark) 1 / 50" manufactured by MOCON) in accordance with JIS-K7126 method B. The oxygen permeability was measured in the direction in which oxygen permeates from the substrate film side to the inorganic thin film layer side.

[0099] (19) Evaluation method for water vapor permeability In each example and comparative example, each laminate film obtained at the stage of laminating the inorganic thin film layer (D) on the base film and the laminated laminate described below were used as samples, and the water vapor permeability was measured in an atmosphere of temperature 40°C and humidity 90%RH using a water vapor permeability measuring device ("PERMATRAN-W 3 / 33MG" manufactured by MOCON) in accordance with JIS-K7129 method B. The water vapor permeability was measured in the direction in which water vapor permeates from the base film side to the inorganic thin film layer side.

[0100] [Preparation of laminated body] A polyurethane adhesive (TM569 / catRT37 manufactured by Toyo-Morton Co., Ltd.) was applied onto the laminates obtained in the Examples and Comparative Examples so that the thickness after drying treatment at 80°C would be 3 μm, and then an unstretched polypropylene film (P1128 manufactured by Toyobo Co., Ltd.; thickness 30 μm; referred to as CPP) was dry laminated on a metal roll heated to 60°C, and aging was carried out at 40°C for 4 days to obtain a laminate gas barrier laminate for evaluation (hereinafter sometimes referred to as "laminate laminate a").

[0101] (20) Evaluation method for laminate strength The laminated laminate prepared above was cut into a width of 15 mm and a length of 200 mm to prepare a test piece, and the laminate strength was measured using a Tensilon universal material testing machine ("Tensilon UMT-II-500" manufactured by Toyo Baldwin Co., Ltd.) under the conditions of a temperature of 23°C and a relative humidity of 65%. The laminate strength was measured at a tensile speed of 200 mm / min, the laminated film layer and the heat-sealable resin layer of each laminated film obtained in the examples and comparative examples were peeled off at a peeling angle of 90 degrees, and the strength was measured when water was dripped onto the peeled part with a dropper (watered) and when it was not dripped (dry).

[0102] (Raw resin / substrate film) Tables 1 to 3 show details of the polypropylene-based resin raw materials used in the following Examples and Comparative Examples, and the conditions for forming the substrate films.

[0103] [Table 1]

[0104] [Table 2]

[0105] [Table 3]

[0106] (Examples 1 and 6, Comparative Examples 2 and 3) For the base layer (A), a polypropylene homopolymer PP-1 shown in Table 1 was used. For the surface layer (B), 43.2% by weight of polypropylene homopolymer PP-1 shown in Table 1, 52.0% by weight of ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 4.8% by weight of master batch A shown in Table 2 were used. At this time, the melt flow rate (g / 10 min) of the polypropylene resin composition constituting the surface layer (B) was 5.1. For the surface layer (C), a mixture of 93.6% by weight of polypropylene homopolymer PP-1 shown in Table 1 and 6.4% by weight of master batch A shown in Table 2 was used. The base layer (A) was made using a 45 mm extruder, the surface layer (B) was made using a 25 mm extruder, and the surface layer (C) was made using a 20 mm extruder. The raw material resins were melted at 250 ° C. and co-extruded from a T-die into a sheet shape, and the surface layer (B) was cooled and solidified so that it contacted a cooling roll at 30 ° C., and then stretched 4.5 times in the machine direction (MD) at 125 ° C. Next, in a tenter, both ends of the film in the width direction (TD) were clamped with clips, preheated at 168 ° C., stretched 8.2 times in the width direction (TD) at 155 ° C., and heat-set at 165 ° C. while relaxing 6.7% in the width direction (TD). The film formation conditions at this time were film formation conditions a. In this way, a biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained. The surface of the surface layer (B) of the biaxially oriented polypropylene film was corona-treated using a corona treatment machine manufactured by Softal Corona & Plasma GmbH at an applied current value of 0.75 A, and then wound up with a winder. The thickness of the obtained film was 20 μm (thickness of surface layer (B) / base layer (A) / surface layer (C) was 1.3 μm / 17.7 μm / 1.0 μm).

[0107] Example 2 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the amount of resin discharged from the extruder was adjusted so that the thickness of the base layer (A) was 15.1 μm and the thickness of the surface layer (B) was 3.9 μm.

[0108] Example 3 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the surface layer (B) was made of a blend of 45.0 wt % polypropylene homopolymer PP-1 shown in Table 1, 52.0 wt % ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 3.0 wt % masterbatch A shown in Table 2.

[0109] Example 4 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the surface layer (B) was made of a blend of 1.2 wt % polypropylene homopolymer PP-1 shown in Table 1, 94.0 wt % ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 4.8 wt % master batch A shown in Table 2.

[0110] Example 5 The polypropylene homopolymer PP-1 used in the base layer (A) and surface layer (C) was changed to PP-2 shown in Table 1, and the film formation conditions were changed to b shown in Table 3. Except for this, the same conditions as in Example 1 were used to obtain a 20 μm biaxially oriented polypropylene film.

[0111] Comparative Example 1 A 20 μm biaxially oriented polypropylene film was obtained under the same conditions as in Example 1, except that the surface layer (B) was made of 95.2 wt % polypropylene homopolymer PP-1 shown in Table 1 and 4.8 wt % masterbatch A shown in Table 2.

[0112] Comparative Example 4 The surface layer (B) was made of a blend of 47.25 wt% polypropylene homopolymer PP-1 shown in Table 1, 52.00 wt% ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, and 0.75 wt% master batch B shown in Table 2. The surface layer (C) was made of a blend of 98.4 wt% polypropylene homopolymer PP-1 shown in Table 1 and 1.60 wt% master batch B shown in Table 2. The same conditions as in Example 1 were used except that the surface layer (C) was formed so that it was in contact with the cooling roll, and a 20 μm biaxially oriented polypropylene film was obtained.

[0113] Comparative Example 5 A biaxially oriented polypropylene film of 20 μm was obtained under the same conditions as in Example 1, except that the base layer (A) was made of 99.0 wt% polypropylene homopolymer PP-1 shown in Table 1 and 1.0 wt% stearyl diethanolamine stearate (KYM-4K, Matsumoto Oil Co., Ltd.) as an antistatic agent.

[0114] Comparative Example 6 The film formation conditions were the same as in Example 1, except that they were changed to c in Table 3, to obtain a 20 μm biaxially oriented polypropylene film.

[0115] The raw materials, production methods, and physical properties of the films used in the above Examples and Comparative Examples are shown in Tables 4 and 5.

[0116] (Inorganic thin film layer) The method for producing the inorganic thin film layer used in each of the Examples and Comparative Examples is described below. The method used in Examples 1 to 6 and Comparative Examples 1, 4 to 6 is shown in Table 3. In Comparative Example 2, no inorganic thin film layer was laminated. (Formation of inorganic thin film layer M-1) Aluminum oxide was vapor-deposited on the base film layer as the inorganic thin film layer M-1. The method of vapor-depositing aluminum oxide on the base film layer was to set the film on the unwinding side of a continuous vacuum deposition machine, run it over a cooled metal drum, and wind the film. At this time, the continuous vacuum deposition machine was depressurized to 10-4 Torr or less, and 99.99% pure aluminum metal was loaded into an alumina crucible from the bottom of the cooling drum, and the aluminum metal was heated and evaporated. Oxygen was supplied to the vapor to cause an oxidation reaction, which was then deposited on the film to form an aluminum oxide film with a thickness of 10 nm.

[0117] (Formation of inorganic thin film layer M-2) As the inorganic thin film layer M-2, a composite oxide layer of silicon dioxide and aluminum oxide was formed on the base film layer by electron beam deposition. As the deposition source, granular SiO2 (purity 99.9%) of about 3 mm to 5 mm and A12O3 (purity 99.9%) were used. The thickness of the inorganic thin film layer (SiO2 / A12O3 composite oxide layer) in the film thus obtained (film containing inorganic thin film layer / coating layer) was 13 nm. The composition of this composite oxide layer was SiO2 / A12O3 (mass ratio) = 60 / 40.

[0118] (Barrier Coat Layer E for Comparative Example 3) Details of the coating liquid for the barrier coat layer E used in Comparative Example 3 are given below.

[0119] [Polyvinyl alcohol resin (A)] To 90 parts by mass of purified water, 10 parts by mass of fully saponified polyvinyl alcohol resin (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name: G Polymer OKS8049Q, (saponification degree 99.0% or more, average polymerization degree 450) was added, and the mixture was heated to 80°C with stirring, and then stirred for about 1 hour. The mixture was then cooled to room temperature, and a nearly transparent polyvinyl alcohol solution (PVA solution) with a solids content of 10% was obtained.

[0120] [Coating solution used for barrier coat layer E] The materials were mixed in the following ratio to prepare a coating liquid (resin composition for barrier coat layer). Ion-exchanged water 35.00% by mass Isopropyl alcohol 15.00% by mass Polyvinyl alcohol resin (A) 50.00% by mass

[0121] [Coating the film with coating fluid (Laminating barrier coat layer E)] The coating solution prepared above was applied onto the corona-treated surface of the substrate film by gravure roll coating, pre-dried at 110°C, and then dried at 140°C to obtain a barrier coating layer E. The coating amount after drying was 0.25 g / m2 (dry). Then, a post-heat treatment was performed at 40°C for 2 days.

[0122] In this manner, a laminate film having an inorganic thin film layer or a barrier coat layer on a substrate film was produced. The obtained laminate film was subjected to various evaluations. The results are shown in Table 5.

[0123] [Table 4]

[0124] [Table 5] [Industrial Applicability]

[0125] According to the present invention, it is possible to provide a laminate film that can form a laminate structure composed of almost a single resin type, mainly polypropylene film, which has a low environmental impact, and that has the necessary performance of gas barrier properties and adhesiveness required for packaging materials. Moreover, since the laminate film of the present invention has few processing steps and is excellent in processability and can be easily produced, it is excellent in both economy and production stability, and a gas barrier film with uniform properties can be provided. [Explanation of symbols]

[0126] 1··Base plate, 2,8··Film holder, 2a··Slot, 2c··Hole, 2d··Slot, 3··Screw, 4,5··Film, 6··Vacuum pump, 7··Pipe, X··Film overlapping part.

Claims

1. A laminated film having a surface layer (B) made of a polypropylene-based resin composition on one surface of a base layer (A) mainly composed of a polypropylene-based resin, a surface layer (C) made of a polypropylene-based resin composition on the other surface of the base layer (A), and further having an inorganic oxide thin film layer (D) laminated on the surface layer (B), wherein the laminated film has a tensile modulus of elasticity in the MD direction of 2.6 GPa or less and a tensile modulus of elasticity in the TD direction of 4.1 GPa or more, and the surface of the laminated film on the inorganic oxide thin film layer (D) side satisfies the following requirements (I) to (V). (I) The arithmetic average roughness (Ra) measured within a 2 μm square area using a scanning probe microscope is 4.5 nm or more and 9.0 nm or less. (II) Martens hardness of 310 N / mm 2 below (III) Water contact angle is 10° or more and 75° or less (IV) The center surface average roughness (SRa) measured by a three-dimensional roughness gauge is 0.010 μm or more and 0.040 μm or less. (V) When the oxygen permeability of the laminated film measured under conditions of 23°C x 65% RH is (A) and the oxygen permeability of the laminated film measured under conditions of 23°C x 80% RH is (B), the barrier value deterioration rate under high temperature and high humidity conditions represented by the following formula is 130% or less. Barrier value deterioration rate (%) under high temperature and high humidity conditions = (B / A) x 100 Formula (1)

2. The oxygen permeability of the laminated film in an environment of 23°C x 65% RH is 60 cc / m 2 ・Water vapor permeability is 4g / m under d·atm or less and 40℃×90%RH environment 2 The laminate film according to claim 1, characterized in that the thickness is d or less.

3. 3. The laminate film according to claim 1, wherein the center surface average roughness (SRa) of the surface layer (C) side of the laminate film measured by a three-dimensional roughness meter is 0.020 μm or more.

4. The Martens hardness of the surface of the surface layer (C) of the laminated film is 270 N / mm 2 4. The laminated film according to claim 1, wherein the film is a laminated film having a thickness of 100 nm or less.

5. The laminate film according to any one of claims 1 to 4, wherein the thickness of the laminate film is 9 µm to 200 µm.

6. A packaging material comprising the laminate film according to any one of claims 1 to 5 and an olefin-based sealant layer laminated on one side of the laminate film.

Citation Information

Patent Citations

  • Production of polypropylene

    JP1992359003A

  • Laminate and its manufacture

    JP2000052501A

  • Body warmer packaging film

    JP2003231221A

  • Metal vapor deposited biaxially stretched polypropylene film

    JP2004168040A

  • Multilayered polypropylene film, laminate and container packaging bag

    JP2006326925A